2020
DOI: 10.1016/j.ijid.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of group A β-hemolytic streptococcal throat carriage and prospective pilot surveillance of streptococcal sore throat in Ugandan school children

Abstract: Objectives: Group A β-hemolytic Streptococcus (GAS), also known as Streptococcus pyogenes, is responsible for an annual 600 million cases of acute pharyngitis globally, with 92% of those infections occurring in low-resource settings. Further knowledge of the acute streptococcal pharyngitis burden in low-resource settings is essential if serious post-streptococcal complicationsrheumatic fever (RF) and its long-term sequel rheumatic heart disease (RHD)are to be prevented. Methods: Two studies were conducted in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 28 publications
3
22
2
Order By: Relevance
“…The 12.9% prevalence of throat GAS colonization found in this study is much higher than that found among 233 children with chronic RHD attending care at a cardiac clinic in Addis Ababa, Ethiopia ( 7 ), but within the reported prevalence among school-going children in sub-Saharan Africa ( 8 – 10 ). Of note, the prevalence of GAS positivity in the study by Zegeye et al ( 7 ) was 6.9%, and the difference between the two studies can mainly be attributed to the fact that all patients in the Ethiopian study were on ARF prophylaxis as compared to the present study where prophylaxis was taken regularly by 29.9% of the total studied population.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…The 12.9% prevalence of throat GAS colonization found in this study is much higher than that found among 233 children with chronic RHD attending care at a cardiac clinic in Addis Ababa, Ethiopia ( 7 ), but within the reported prevalence among school-going children in sub-Saharan Africa ( 8 – 10 ). Of note, the prevalence of GAS positivity in the study by Zegeye et al ( 7 ) was 6.9%, and the difference between the two studies can mainly be attributed to the fact that all patients in the Ethiopian study were on ARF prophylaxis as compared to the present study where prophylaxis was taken regularly by 29.9% of the total studied population.…”
Section: Discussioncontrasting
confidence: 67%
“…This is more serious for those who are particularly at a greater risk due to a number of factors including their genetic susceptibility, which renders them more sensitive to infection with a rheumatogenic strain of GAS ( 25 ). Only few studies from sub-Saharan Africa have reported the prevalence of GAS colonization in the general population ( 8 – 10 , 22 , 26 ), in patients with pharyngotonsillitis ( 27 , 28 ), and among RHD patients ( 7 ). The present study therefore adds to the current knowledge on RHD in the region by demonstrating that among RHD patients attending care at a tertiary health facility in Tanzania, throat GAS colonization is present in 12.9% and is independently associated with stopping ARF prophylaxis among these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to domestic transmission, other environments with a high risk of transmission include public areas, such as schools, barracks, and kindergartens. [15] Especially in acute forms, the disease usually spontaneously regresses in a week without the addition of antibiotics to treatment. However, in the presence of severe complications, including acute rheumatic fever and glomerulonephritis, it is recommended to start penicillin treatment without waiting for the culture result, and Hanage et al stated that resistant strains were developing in patients that did not respond to treatment.…”
Section: Resultsmentioning
confidence: 99%